Praktik Pemberian Asi Eksklusif Pekerja Wanita Di Universitas Muhammadiyah Surabaya - Ma’rifah, Umi; Anifah, Fulatul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: Â aims to describe the practice of exclusive breastfeeding for female workers at the University of Muhammadiyah Surabaya.Methods: The research design is descriptive quantitative, the sampling technique is total sampling. The research sample was female workers at the University of Muhammadiyah Surabaya who breastfeed babies aged 6-12 months as many as 22 people. Data collection in October-April 2020 using a questionnaire and structured interview guidelines with Google Form. The data results are presented in the form of a frequency distribution table.Results: . The results showed that from 22 respondents, there were 13 respondents (59.1%) who succeeded in giving exclusive breastfeeding, 9 respondents (40.9%). The practice of exclusive breastfeeding of female workers at the Muhammadiyah University of Surabaya is more successful and there are still some that are not. Conclusion: Â The success of exclusive breastfeeding is supported by the management of breastfeeding from the start of the leave period and when work is done well, besides that, most of the support from co-workers is very good. Although there is no dedicated room for expressing breast milk at work, most of the respondents have expressed breast milk regularly on average 3-4 times per day with a more flexible time.